ANALISIS INDEKS KEPUASAN MASYARAKAT DI KANTOR KECAMATAN PALARAN KOTA SAMARINDA - . Emi (Jurnal Paradigma (JP), 2017)
This article aim to identify and analyze the Community Satisfaction Index (HPI) to public service organized by the District Office Palaran. Besides, this study also aimed to determine the factors supporting and hindering the implementation of public services at the District Office Palaran. This study uses a combined approach between quantitative and qualitative descriptive. A quantitative approach using the sample population as a source of data while the qualitative approach featuring informant as speakers or participants in answering the problem of research. The results showed that the average percentage method, Community Satisfaction Index (HPI) to public service organized by the District Office Palaran is 70.1%, this means that the quality of public services produced in the category quite well. While the results of the analysis by the method of the weighted average value, generating Community Satisfaction Index (HPI) to public service organized by the District Office Palaran with a score of 87.25, which means the value perception and quality of public services organized by the District Office in the category Palaran very Good (Grade A).Keywords: public service, community satisfaction index